The Readiness of Primary Health Centers (Puskesmas) to Provide Maternal and Newborn Services in West Bangka, Indonesia - Ahmad Azmul Asmar Irfan; Christian Ezra Kestito; Amalia Sainsiana; Ananda Hadist Wahyudi; Lyliani Khairunnisa; Fathia Azzahra (The Avicenna Medical Journal, 2025)
Background: Maternal and neonatal mortality remain a pressing public health concern in Indonesia, particularly in rural districts such as West Bangka. The district maternal mortality rate (MMR) has risen steadily, reaching 212.44 per 100,000 live births in 2022, while the neonatal mortality rate (NMR) has climbed from 3.7 to 7.89 per 1,000 live births between 2018 and 2022. This study evaluates the availability and readiness of Primary Health Centers (Puskesmas) in West Bangka to deliver maternal and newborn health services. This study aims to assess the service availability and readiness of all eight Puskesmas in West Bangka Regency using the WHO Service Availability and Readiness Assessment (WHO-SARA) instrument. Methods: A facility-based cross-sectional study was conducted between July and August 2024 across all 8 Puskesmas in West Bangka. Data were collected through structured interviews with key health personnel and direct observation guided by the WHO-SARA framework. Readiness was assessed across two service areas (antenatal care (ANC) and obstetric-neonatal care) and within each service area, evaluated across four readiness domains: staff training and clinical guidelines, equipment and supplies, diagnostic capacity, and essential medicines and commodities. For obstetric and neonatal care, a fifth domain covering basic emergency obstetric and neonatal care capacity was additionally assessed. Results: The mean overall readiness score across all Puskesmas was 86.0 (range: 62.0-92.1). Seven of 8 Puskesmas (87.5%) achieved scores above the 75-point threshold, qualifying as “optimal.” Puskesmas Mentok achieved the highest overall score (92.1), while Puskesmas Puput was the sole suboptimal facility (62.0), largely owing to deficiencies in staff training and basic obstetric and newborn care (42.9). Key gaps identified across facilities included the absence of manual vacuum extractors (0%) and limited availability of intermittent preventive treatment for malaria in pregnancy (IPTp) protocols (37.5%) and trained IPTp staff (12.5%). Conclusions: Most Puskesmas in West Bangka demonstrate adequate readiness for maternal and newborn health services. However, Puskesmas Puput requires urgent targeted intervention. System-wide gaps in IPTp capacity, obstetric equipment, and staff training represent priority areas for policy action and resource allocation.   Keywords: Maternal and neonatal services, primary health care, Puskesmas, WHO-SARA, facility assessment